2016
DOI: 10.18697/ajfand.76.15540
|View full text |Cite
|
Sign up to set email alerts
|

Using farmer-prioritized vertisol management options for enhanced green gram and tomato production in central Kenya

Abstract: Green gram (Phaseolus aures L.) and tomato (Solanum lycopersicum L) are widely grown in the vertisols of the Mwea Irrigation Scheme in Kenya alongside the rice fields. Green gram can fix nitrogen and is grown for its highly nutritious and curative seeds while tomato is grown for its fruit rich in fiber, minerals and vitamins. The two can be prepared individually or together in a variety of ways including raw salads and/or cooked/fried. They together form significant delicacies consumed with rice, which is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…[84] found that soil pH negatively correlated with available zinc levels. In the MIS, instances of continuous waterlogging due to inadequate drainage infrastructure have been reported, particularly in areas with black cotton soils containing high clay content [85]. Such persistent flooding prevalent in cluster MW, is commonly associated with low soil pH [86,74].…”
Section: Micronutrientsmentioning
confidence: 99%
“…[84] found that soil pH negatively correlated with available zinc levels. In the MIS, instances of continuous waterlogging due to inadequate drainage infrastructure have been reported, particularly in areas with black cotton soils containing high clay content [85]. Such persistent flooding prevalent in cluster MW, is commonly associated with low soil pH [86,74].…”
Section: Micronutrientsmentioning
confidence: 99%